EPO rs1617640 A>C is a Protective Factor for Chronic Obstructive Pulmonary Disease: A Case Control Study - Yunchao Wang; Zhi Li; Xiaoyi Zhang; Ao Lin; Cuiyi Chen; Xiaobin Zeng; Yujie Pan; Chun Mao; Chenli Xie; Dongsheng Huang; Yibin Deng; Xuhui Zhang; et al. (Frontiers in Bioscience-Landmark, 2023)
Background: The occurrence and development of chronic obstructive pulmonary disease (COPD) are regulated by environmental and genetic factors. In hypoxia, Erythropoietin (EPO) satisfies the body’s need for oxygen by promoting the production of red blood cells. Hypoxia was proven to be a common physiological condition in COPD progression and associated with many complications. Some studies have found that EPO is involved in the development of COPD. But the mechanism has not been fully proven. Methods: We conducted a case-control study enrolled 1095 COPD patients and 1144 healthy controls in Guangdong Province to evaluate the association between EPO polymorphisms (rs1617640 A>C, rs507392 A>G, rs564449 G>T) and COPD susceptibility. 872 participants from southern Gansu Province were recruited to verify the effect of EPO polymorphisms on lung function. Results: EPO rs1617640 C allele reduced COPD susceptibility in southern Chinese significantly (AC vs. AA: adjusted Odds ratio (OR) = 0.805, 95% CI = 0.669–0.969; AC+CC vs. AA: adjusted OR = 0.822, 95% CI = 0.689–0.980). However, there was no association between rs507392 A>G and rs564449 G>T polymorphisms and COPD susceptibility (p > 0.05). We further observed that the rs1617640 C allele was associated with higher FEV1 and FVC in Guangdong and Gansu populations significantly (both p < 0.05). In brief, the level of FEV1 and FVC increased with the C allele number. We modeled the relative risk for men and women, in which the population-attributable risks chances were 0.449 (0.258–0.641) and 0.262 (0.128–0.396) respectively. In this model, smoking status, coal as fuels, education level, and rs1617640 A>C were finally retained for males, while smoking status, biomass as fuels, and1617640 A>C were retained for females. In the end, using the method developed by Gail and Bruzzi, we fitted a 10-year absolute risk model for southern Chinese with different individual relative risks, which was presented as a table. Conclusions: In conclusion, this study found that EPO rs1617640 A>C polymorphism is associated with COPD susceptibility in southern Chinese, and the C allele was associated with better lung function. In addition, it could also be considered a genetic marker associated with environmental factors to predict the absolute 10-year risk of COPD in southern Chinese.